Study guides

Q: How do you simplify this expression 4p plus 9 plus 7p plus 2?

Write your answer...

Submit

Related questions

4p + 9 - 7p + 2 4p - 7p + 9 + 2 p(4 - 7) + 9 + 2 -3p + 11

4p + 9 + (-7p) + 2 = 4p - 7p + 9 + 2 = -3p + 11

11p+11

It is: 11p+11 simplified

4p+9-7p+2 -3p+11 p = 11/3

15 + 3 = 7p - 4p ie 18 = 3p so p = 6

2p+7p = 9p simplified

p=-3

7p+2 is an algebraic expression. Since it is neither an equation nor an equality, it cannot have a solution or answer.

i dont know

8p-p-4p= 7p-4p= 3p

8

The expression can be simplified to: -8p--29

3p - 8 = 13 - 4p : Add 4p to both sides 7p - 8 = 13 : Add 8 to both sides 7p = 21 : Divide both sides by 7 p = 3.

If you mean: 7p-3p+4-2 = 2p-1+10 => 4p+2 = 2p+9 => 2p = 7 Therefore: p = 7/2 => p = 3.5

6nx + 7p - 14p + 2nx + 6x = 8nx - 7p + 6x

-7p2 -2p3 + 5 is an expression, not an equation or inequality. An expression cannot be solved

5p + 15p + 7p = 27p 5p - 15p + 7p = -3p 5p x 15p + 7p = 75p2 + 7p 5p/15p + 7p = 7p + 1/3

8p+5 = 11+7p= 8p-7p = 11-5p = 6

14 + 6p = 6 + 7p 8 = p

7p + 2 = 5p + 8 7p - 5p = 8 - 2 2p = 6 p = 3

The question contains an expression, not an equation (nor inequality). An expression cannot be solved.

7p+5t

Seven multiplied by the variable "p"

-7p + 5r - 6p + 3r = -7p - 6p + 5r + 3r = -(7 + 6)p + (5 + 3)r = -13p + 8r